Droga na Downing Street. Uwagi nad karierę polityczną Margaret Thatcher - Kosman, Marceli (Przegląd Politologiczny, 2018)
The road of Margaret Thatcher (born in 1925) to her political career and winning the tell- ing nickname of the ‘Iron Lady’ has commonly been described as exceptional in the recent history of the Old Continent. The first woman to head a great European democracy, she served as Prime Minister three times, winning general elections and heading the government of Great Britain for eleven years (1979-1990). This was a record-breaking result in the history of the UK, which she managed, surrounded by a team of consummate coworkers whom she clearly dominated. Thatcher is included in a small circle of the most outstanding statespeople in her country, in particular compared to Winston Churchill. Despite not having aristocratic origins, she won the highest office in the government of Her Majesty Elizabeth II thanks to her talent, diligent work, ambition, and experience gath- ered in the positions she successively held. Her career in the Conservative Party lasted many years. Her vision of transformations in the political system of the state was based on her own experience and the advice of devoted workers, who she selected using her intuition. Her hus- band, Denis Thatcher, played an important role by her side, yet he always remained in the background, providing support and playing the role of a reasonable private advisor. The author emphasizes the high political culture of Margaret Thatcher and her circle, and he also underlines Polish elements in her policy. He pays a lot of attention to her excellent memoires as a source for politological studies, and to a review of the latest movie about the ‘Iron Lady’.